Aplikasi IoT Untuk Monitoring Kualitas Air Tawar Pada Pemeliharaan Ikan Dengan Metdoe Fuzzy Logic Berbasis Aduino - Sendi Novianto; Muhammad Naufal Taqiyuddin (Fakultas Teknik Universitas Hamzanwadi, 2026)
Freshwater fish farming requires a lot of attention. Water conditions are the main consideration when raising fish. Water conditions, including pH, ammonia, and temperature, will affect fish development. Monitoring water conditions is not always possible visually and on-site. Therefore, a reader connected to the internet is needed so we can read the exact values ​​and monitor anywhere and anytime. This is where the Internet of Things (IoT) plays a crucial role in facilitating freshwater fish farming monitoring. Applications are also used to display data from the existing Internet of Things (IoT). The presence of the Internet of Things (IoT) will increase efficiency in fish farming and facilitate monitoring. The Mamdani Fuzzy Logic method will be implemented and embedded in the ESP32 as a microcontroller. The results of this research are an Internet of Things (IoT) tool along with a website as a data monitoring page. The tool will be tested using Mean Absolute Percentage Error (MAPE) compared to the results of calculations in Matlab. The results showed only a small error between the tool readings and Matlab with an accuracy level of 99%. In conclusion, this tool can help the efficiency of water quality monitoring in fish farming with a reading accuracy and fuzzy logic processing rate of 99%.